DISTRIBUTION OF PANTOTHENIC ACID IN FISH. - CHHATBAR, SUDHIR K; VELANKAR, N K (Fishery Technology, 2017)
The distribution of pantothenic acid in free and bound forms in various fish species is reported. It is observed that the fish muscle contains on an average about 12.0fi g. pantothenic acid per g. About 60% of the panthothenic acid is present in the bound form as coenzyme A in the fish skeletal muscle.